'Climate crisis' and 'bushfire disaster': Implications for tourism from the involvement of social media in the 2019–2020 Australian bushfires. (June 2020) - Schweinsberg, Stephen; Darcy, Simon; Beirman, David
Abstract: This research note seeks to draw attention to the potential impact of social media climate change debates on the Australian tourism industry during and after the devastating 2019–2020 Australian bushfires. Whilst acknowledging the tremendous role of all media forms in the emergency management response, the present paper argues that the growing prevalence of climate change discourse in social media has precipitated a dilemma for communities and industries in fire affected regions. Can the tourism industry continue to always classify itself as a passive victim of catastrophic bushfire disasters? Or do we, as a collective tourism entity, need to embrace our culpability for helping cause a climate crisis that so many people in the community deem as being a contributing factor for the severity of the fire season? In this research note we will consider these issues in the context of literature on social licence to operate.